A short hand of Prime number distribution - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
This is a short paper to demonstrate how complacent scientists and mathematicians have been and how complacent the mysteries of the sciences are (actually there are no mysteries, the almighty has made mathematics and the sciences in our image) .This is simple mathematics, including the mathematics of the unified theorem that follows this paper, that mathematicians have botched for 500 years. This is also made possible by a unique prime number sieve that is continuum at 6 and 1:3, the denOtter- Hope research continuous sieve for prime numbers, the most accurate prime number sieve. Whilst the discovery of large prime number does nothing for the understanding of prime numbers, the short hand does. We have presented a short series and if so called mathematicians cannot extend the series mathematically, they should join a historical line of western mathematicians that convoluted the reality of mathematics on prime numbers for 500 years.